2022
DOI: 10.7554/elife.70240
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota induces high platelet response in patients with ST segment elevation myocardial infarction after ticagrelor treatment

Abstract: Background:Ticagrelor is a first-line drug for the treatment of acute ST elevation myocardial infarction (STEMI). However, approximately 20% STEMI patients taking ticagrelor exhibited a delayed response and the mechanism was still unclear.Methods:To explore the mechanism of the poor response of ticagrelor in post-percutaneous coronary intervention (PCI) patients, we enrolled 65 high platelet reactivity (HPR) patients and 90 controls (normal platelet reactivity [NPR]). Pharmacokinetic assessment result showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…More than 20% metabolites were significantly associated with platelet activation markers and the majority involved lipids. In a more recent study, clinical findings with experimental data suggested that gut microbiota dysbiosis may be an important mechanism for the high platelet reactivity in patients treated with ticagrelor, a first-line drug for the treatment of acute ST elevation myocardial infarction ( 16 ). For example, the abundance of gut microbiota species Methylbacillus , Sphingomonas , and Staphylococcus was negatively correlated with serum salicylate, which was previously found to induce ITP and inhibit platelet production in megakaryocytes ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 20% metabolites were significantly associated with platelet activation markers and the majority involved lipids. In a more recent study, clinical findings with experimental data suggested that gut microbiota dysbiosis may be an important mechanism for the high platelet reactivity in patients treated with ticagrelor, a first-line drug for the treatment of acute ST elevation myocardial infarction ( 16 ). For example, the abundance of gut microbiota species Methylbacillus , Sphingomonas , and Staphylococcus was negatively correlated with serum salicylate, which was previously found to induce ITP and inhibit platelet production in megakaryocytes ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of metaorganismal circuits have been reported to modulate different aspects of cardiovascular and cardiometabolic conditions, such as arterial hypertension and hypertensive end organ damage ( 3 , 4 ), lipid metabolism and atherosclerosis ( 5 , 6 ), glucose metabolism ( 7 ), platelet activation and thrombus formation ( 8 10 ), and ischemic heart disease ( 11 ). Remarkably, recent studies suggest that gut microbial composition also impacts on the efficacy of cardiovascular pharmacotherapy ( 12 , 13 ). Targeting of distinct gut microbial pathways may help to establish novel strategies in preventing cardiometabolic and cardiovascular diseases.…”
mentioning
confidence: 99%
“…Intriguingly, gut microbial diversity might even affect cardiovascular disease therapies as shown for ticagrelor by a recent study on the efficacy of anti-platelet treatment in STEMI (113). Moreover, it was shown that chronic statin therapy is linked to lower prevalence of microbiota dysbiosis (109,110). In addition to above, abnormal gut microbiome homeostasis could be linked to development of chronic effects from viral infections (111).…”
Section: Accepted Manuscriptmentioning
confidence: 99%